Datanet 1 en de convergentie van computer en telecommunicatie - de Wit, Onno (Studium, 2008)
Datanet 1 and the convergence of the computer and telecommunications  This article describes the efforts of the Dutch national company for telecommunication, PTT, in introducing and developing a public network for data communication in the Netherlands in the last decades of the twentieth century. As early as the 1960s, private companies started to connect their local computers. As a result, small private computer networks started to emerge. As the state company offering general access to public services in telephony, the PTT strove to develop a public data network, accessible to every user and telephone subscriber. This ambition was realized with Datanet 1, the public data network which was officially opened in 1982. In the years that followed, Datanet became the dominant network for data transmission, despite competing efforts by private companies and computer manufacturers. The large-scale application of Datanet in public municipal administration serves as a case study for the development of data communication in practice, that shows that there was a gradual migration from X-25 to TCP/IP protocols. The article concludes by stating that the introduction and development of data transmission transformed the role of the PTT in Dutch society, brought new working practices, new services and new responsibilities, and resulted in a whole new phase in the history of the computer.